Development of a categorical naming test in Korean: Standardization and clinical application for patients with stroke - Hwang, Yu Mi (PLoS One, 2021)
PURPOSE: The purpose of this study was to develop and standardize a new categorical naming test, titled the Categorical Naming Test (CNT), for stroke patients, and to investigate its validity and clinical usefulness for patients with stroke. MATERIALS AND METHODS: The CNT was developed based on semantic category, imageability, and psycholinguistic factors such as word frequency and word length. The test materials included two main semantic categories (living objects and artificial objects) comprising 60 items. We standardized the CNT on 221 healthy adults and administered the CNT to 112 stroke patients. RESULTS: Internal consistency and concurrent validity of the test were high. The mean total CNT scores varied significantly according to participants’ age, sex, and education. Among healthy controls, the scores for naming living objects were significantly higher than those for artificial objects. The analysis of stroke patients showed that the total CNT score revealed a statistically significant difference based on the patients’ lesion laterality and presence of aphasia, after controlling for age, sex, and education. However, the categorical scores achieved by comparing the naming scores for living and artificial objects showed no significant differences according to lesion laterality, stroke type, and presence of aphasia. CONCLUSION: The CNT is a newly developed version of an overt naming task with high internal consistency validity for stroke patients in Korea. The newly developed CNT can prove useful in evaluating naming ability in stroke patients.